Effect of Glycine and TT-LYK in Alkaline CMP Slurry on Controlling the Galvanic Corrosion at Al-Co Interface. (1st January 2019) - Wang, Zhi; Sun, Ming; Niu, Xinhuan; Cui, Yaqi; Zhou, Jiakai; Meng, Fanhao; Zhou, Wanqing
Abstract : As the feature size of integrated circuit (IC) shrinks down to 28nm and below, aluminum (Al) is considered to be one of the suitable gate materials, and cobalt (Co) is considered to be one of the suitable barrier materials. During chemical mechanical polishing (CMP) of the Al-Co gate, galvanic corrosion can occur when two kind of metals with a large open circuit potential (Eoc) difference contact with each other within the device architecture and are exposed to charge conducting CMP slurries. Al is severely corroded as an anode in the presence of Co because the standard electrode potential (E = −1.66 V) is lower than that of Co (E = −0.27 V). In this paper, using the advantages of different materials in adsorption and dissolution of different metal, the effect of glycine and TT-LYK (TT) with different concentrations on galvanic corrosion of Al and Co was studied by potentio dynamic and static polarization measurements with impedance monitoring. The potential different between Al and Co electrodes was significantly reduced for selective adsorption characteristics of the complex formed by glycine with Al and Co significantly reduced the potential difference between Al and Co electrodes. The substances formed by TT with Al and Co can be adsorbed on both surfaces well, and the current difference between Al and Co electrodes can be significantly reduced due to the difference in solubility of the reactants. When glycine and TT were used synergistically, the dynamic corrosion potential (Ecorr ) difference between Al and Co electrodes was reduced to 10 mV, and the static Ecorr difference was reduced to 17 mV with glycine concentration of 1000 ppm and TT concentration of 100 ppm. The dynamic corrosion current (Icorr ) difference was 0.587μA/cm 2, and the static Icorr difference was 2.361μA/cm 2 .